Improving the Efficiency of the AIS System Using Algorithms for Dealing Signal Collisions - Makarov, S. B.; Zavjalov, S. V.; Volvenko, S. V.; Kuznetsova, A. A.; Lavrenyuk, I.; Eremenko, Iu.E.; Aharonyan, A. K.; Avetisyan, V. H.
The paper considers methods for receiving and processing automatic identification of ships (AIS) signals by a small satellite (CubeSat). A comparison of various methods for reducing the impact of collisions on the reliability of reception is given, such as the choice of orientation and type of the CubeSat receiving antenna, the use of various demodulation algorithms that take into account the presence of Doppler frequency shifts, as well as decollision processing algorithms. Using simulation modeling that takes into account the parameters of the space scenario (orbit altitude, antenna type, etc.), the efficiency of the considered methods in terms of reducing the packet error in the presence of first-order collisions is shown.
Keywords: Algorithm; Space